Untreated head and neck cancer: Natural history and associated factors. Issue 1 (11th September 2020) - Zolkind, Paul; Lee, Jake J.; Jackson, Ryan S.; Pipkorn, Patrik; Massa, Sean T.
Abstract: Background: This study aims to provide modern estimates of survival for untreated head and neck cancer (HNC) and to identify patient‐ and tumor‐specific factors associated with not receiving definitive treatment. Methods: Adults with mucosal HNC were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Median overall survival of untreated patients was calculated and stratified by site and stage. Cause‐specific survival and factors associated with no treatment were investigated with advanced statistics. Results: The study cohort included 6477 patients who received no treatment. Overall, untreated patients had a median survival of 12 months, with significant variability by site and stage. Multivariable analysis identified advanced age, black race, unmarried status, and lack of private insurance as associated with no treatment. Conclusions: Survival of HNC without treatment is dismal, yet substantial variation exists by tumor site and stage. Higher rates of no treatment among the poor and racial minorities are potentially driven by disparities in care availability and provision.